2023
DOI: 10.1002/cmdc.202200490
|View full text |Cite
|
Sign up to set email alerts
|

Application of Phosphoramidate ProTide Technology for the Synthesis of 5’‐mRNA Cap Analogs Modified on the Exocyclic Amine Group

Abstract: Aryloxy triester phosphoramidate methodology, commonly known as ProTide technology, is one of the most widely used prodrug approaches applied to therapeutic nucleosides. This approach has been used extensively by the pharmaceutical industry and researchers in medicinal chemistry. Herein we report our adaptation of this effective method for the synthesis of bioactive 5'-mRNA cap analogues as inhibitors for targeting cap-dependent translation. The synthesis was performed in two main stages: preparation of N2-mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There are three well‐known methods for the synthesis of ProTides, namely coupling of the nucleoside to a diarylphosphite with subsequent oxidative amination, phosphorylation with a phosphorochloridate reagent, or coupling of an amino acid to a nucleoside aryl phosphate [13] . In our case, p ‐nitrophenol phosphoramidate 5 was chosen as aryl phosphate reagent [26] . This is in contrast to earlier methods of McGuigan et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three well‐known methods for the synthesis of ProTides, namely coupling of the nucleoside to a diarylphosphite with subsequent oxidative amination, phosphorylation with a phosphorochloridate reagent, or coupling of an amino acid to a nucleoside aryl phosphate [13] . In our case, p ‐nitrophenol phosphoramidate 5 was chosen as aryl phosphate reagent [26] . This is in contrast to earlier methods of McGuigan et al .…”
Section: Resultsmentioning
confidence: 99%
“…[13] In our case, p-nitrophenol phosphoramidate 5 was chosen as aryl phosphate reagent. [26] This is in contrast to earlier methods of McGuigan et al that employed phosphorchloridates as reagents in this step. [27,28] To accomplish our synthesis, the ethylbutyl ester of alanine was prepared in 91 % yield by reacting alanine with 2-ethylbutanol in toluene in the presence of tosylic acid as catalyst.…”
Section: Synthesismentioning
confidence: 87%
“…First in this class was 4Ei-1, a prodrug that is transformed intracellularly into the functional 7-benzylguanosine monophosphate (bn 7 GMP, 1, Figure 1) [19]. Bn 7 GMP is the flagship example of cap analogues that have been used to prepare various types of pro-drugs [20,21]. Since generally, monophosphate cap analogues exhibit poor translational inhibitory properties, an additional modification of these structures is required to compensate for this deficit and a modification of the N7 guanosine position is one of the chosen sites.…”
Section: Introductionmentioning
confidence: 99%
“…Another type of modification that makes the monophosphate a potent inhibitor is those introduced at the N2 position of m 7 G, which have also been verified and tested in the ProTide form [20]. Studies have shown that a single substitution at the N2 position of the m 7 G monophosphate leads to increased translational inhibition [23].…”
Section: Introductionmentioning
confidence: 99%